Mycobacterium ulcerans treatment--can antibiotic duration be reduced in selected patients? - Raquel Cowan; Eugene Athan; N Deborah Friedman; Andrew J Hughes; Anthony McDonald; Peter Callan; Janet Fyfe; Daniel P O'Brien (Public Library of Science (PLoS), 2015)
INTRODUCTION:Mycobacterium ulcerans (M. ulcerans) is a necrotizing skin infection endemic to the Bellarine Peninsula, Australia. Current treatment recommendations include 8 weeks of combination antibiotics, with adjuvant surgery if necessary. However, antibiotic toxicity often results in early treatment cessation and local experience suggests that shorter antibiotic courses may be effective with concurrent surgery. We report the outcomes of patients in the Barwon Health M. ulcerans cohort who received shorter courses of antibiotic therapy than 8 weeks. METHODOLOGY / PRINCIPAL FINDINGS:A retrospective analysis was performed of all M. ulcerans infections treated at Barwon Health from March 1, 1998 to July 31, 2013. Sixty-two patients, with a median age of 65 years, received < 56 days of antibiotics and 51 (82%) of these patients underwent concurrent surgical excision. Most received a two-drug regimen of rifampicin combined with either ciprofloxacin or clarithromycin for a median 29 days (IQR 21-41 days). Cessation rates were 55% for adverse events and 36% based on clinician decision. The overall success rate was 95% (98% with concurrent surgery; 82% with antibiotics alone) with a 50% success rate for those who received < 14 days of antibiotics increasing to 94% if they received 14-27 days and 100% for 28-55 days (p<0.01). A 100% success rate was seen for concurrent surgery and 14-27 days of antibiotics versus 67% for concurrent surgery and < 14 days of antibiotics (p = 0.12). No previously identified risk factors for treatment failure with surgery alone were associated with reduced treatment success rates with < 56 days of antibiotics. CONCLUSION:In selected patients, antibiotic treatment durations for M. ulcerans shorter than the current WHO recommended 8 weeks duration may be associated with successful outcomes.